Facts and fallacies of ACL injuries in women
In many sports, non-contact ACL injuries occur more frequently in women than in men. In fact, there is a four times increase in incidence of this injury in women`s soccer and twice the incidence in women`s basketball. Intrinsic risk factors such as joint laxity, limb alignment, femoral notch dimension, hormonal influences, and genetics and extrinsic factors including strength variations between the sexes, neuromuscular control, body movement and shoe surface interface have been proposed for this increased incidence. However, there is still controversy over the exact role and significance of each of these factors. A clear understanding of risk factors is important since preventative programs can only be devised once such factors are better understood. If an ACL injury does occur management guidelines including factors to be considered in selecting operative versus non-operative care are generally similar for males and females although some data does indicate that differences in biological responses between the sexes may somewhat alter post operative outcomes and responses to rehabilitation. This symposium will discuss risk factors, treatment options and rehabilitation protocols for women who sustain non-contact ACL injuries.